KONTROL DIRI, ORIENTASI SEKSUAL, DAN SUBJECTIVE WELL-BEING PADA REMAJA YANG MENGALAMI FATHERLESS - Imanuela Angela Serena Putri; Arthur Huwae (Media Bina Ilmiah, 2025)
Adolescents who experience fatherlessness will affect their lives so that it can also affect their subjective well-being problems. This study aims to determine the relationship between self-control and sexual orientation with subjective well-being in adolescents who experience fatherlessness. The research uses a quantitative approach method with a multiple correlation analysis design. The samples are fatherless adolescents. The samples involved were 113 people and obtained using a representative method. The research instrument consists of Self Control Scale (SCS), Klein Sexual Orientation Grid (KSOG), Satisfaction With Life Scale (SWLS). The results prove that self-control and sexual orientation are not the predictors of subjective well-being for adolescents who experience fatherlessness